K-Pop fan solidarity in Indonesian social discourse: Activism and power resistance - Nadhifah, Nurul Laili; Budiman, Manneke; Tambunan, Shuri Mariasih Gietty (Privietlab, 2026)
Fandom activism refers to the ways fans engage with social, cultural, and political issues that affect their daily lives. Over time, social media has reshaped fan activism by altering fans’ roles within the entertainment industry and amplifying their presence in society, including in Indonesia. Using digital ethnography, this study focuses on key moments in the K-pop fandom in Indonesia, such as the DAY6 and ELF conflicts with a concert promoter and the protest against the 12% VAT increase. This study demonstrates how fandom activism serves as a framework for resisting dominant powers, overcoming the negative stigma of a patriarchal society, and adapting to evolving patterns of activism across generations. These findings highlight the complex interplay between the internal and external dynamics that shape K-pop fan activism in Indonesia. Fans continually renegotiate their identities and roles within fan communities and society at large.